Pengaruh Panjang Jaringan Terhadap Drop Tegangan Pada Penyulang Duku dan Kurma PT. PLN (Persero) ULP Rumbia - Afrida, Yenni; Jeckson (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2024)
Voltage drops in distribution systems can occur in medium voltage networks (JTM), distribution transformers, low voltage networks (JTR) and house lines. Voltage drops in the network cause suboptimal distribution and increase power losses. PT. PLN (Persero) ULP Rumbia has two feeders with pure radial network characteristics sourced from the Seputih Banyak Main Substation. The length of the Duku Feeder network has a voltage of 96.8 KMS with a load of 150 A while the length of the Kurma Feeder network is 207.21 kV with a load of 155 A. The network reconfiguration of the Dente Teladas Substation was carried out to shorten the network length. This research aims to calculate the voltage drop that occurs at the Duku and Kurma feeders before and after network configuration. This research uses the quantity method to compare the calculation results with the voltage drop standards set by PT. PLN (Persero). After reconfiguring the Duku and Kurma feeders, there was an increase in tip voltage which indicated improvement. From the calculation results before adding the network to the Duku feeder, the voltage at the receiving end was 19.5 kV with a voltage drop of 7.1%, and at the Kurma feeder the voltage at the end of the line was 17 kV with a voltage drop of 19%. This is clearly no longer in accordance with the local TMP, and requires further study to overcome this problem. The voltage on the two feeders goes through a step up process using a Medium Voltage OLTC (On Load Tap Changer) so that the voltage on each feeder becomes between 19.86 kV to 20.16 kV.